Integration of Mobile Perceived Compatibility, Mobile Perceived Financial Resources, and Mobile Perceived System Quality with TAM in Virtual Hotel Operator Applications in Indonesia - Prakarsa, Graha; Nasution, Vani Maharani; Ramadhiana, Irena Nurul; Ginanjar, Ari Ramdan (iora, 2020)
The development of current technology makes people want to book hotel rooms that suit their own needs and desires, then the VHO application in Indonesia comes. This causes the need for a model that is able to measure the extent to which the level of acceptance of VHO applications. The existence of a measurement model for the acceptance of the VHO application will greatly help business people in this field to be able to develop their products and improve the performance of the service products they offer. The purpose of this research is to determine how much acceptance of VHO application users based on the Technology Acceptance Model (TAM). This research approach uses a quantitative approach with survey methods. The data collection technique is using a questionnaire that distributed randomly to users of the VHO application. The data analysis method used is descriptive analysis, using multiple linear regression techniques. The results of this study indicate that the variables of mobile perceived compatibility, mobile perceived financial resources, and mobile perceived system quality have a simultaneous effect on the mobile variable perceived usefulness, the mobile variable perceived ease of use and the intention to use variable.